2012
DOI: 10.3892/or.2012.2165
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor and anti-angiogenesis effects of thymoquinone on osteosarcoma through the NF-κB pathway

Abstract: Thymoquinone (TQ), the predominant bioactive constituent derived from the medicinal spice Nigella sativa (also known as black cumin), has been applied for medical purposes for more than 2,000 years. Recent studies reported that thymoquinone exhibited inhibitory effects on the cell proliferation of several cancer cell lines. This study was performed to investigate the antitumor and anti-angiogenic effects of thymoquinone on osteosarcoma in vitro and in vivo. Our results showed that thymoquinone induced a higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
93
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(99 citation statements)
references
References 28 publications
5
93
0
1
Order By: Relevance
“…It was concluded that TQ effectively inhibits tumor growth and angiogenesis both in vitro and in vivo. Therefore, inhibition of NF-κB and downstream effector molecules is a possible underlying mechanism of the antitumor and anti-angiogenic activity of TQ in osteosarcoma [57] .…”
Section: Anticancer Activitymentioning
confidence: 99%
“…It was concluded that TQ effectively inhibits tumor growth and angiogenesis both in vitro and in vivo. Therefore, inhibition of NF-κB and downstream effector molecules is a possible underlying mechanism of the antitumor and anti-angiogenic activity of TQ in osteosarcoma [57] .…”
Section: Anticancer Activitymentioning
confidence: 99%
“…In this study, it was observed that ethanolic leaf extract of marine alga S. wightii effectively inhibited HUVEC cell tube formation. Recent study reported by Peng et al, 2013 confirmed that a phytochemical, thymoquinone from Nigella sativa can inhibit tumor angiogenesis and was able to prevent osteosarcoma cell growth in a mouse osteosarcoma model.…”
Section: Discussionmentioning
confidence: 83%
“…The inhibitory effect of the ethanolic leaf extract of S. wightii on the viability of osteosarcoma cells was performed as reported previously (Peng et al, 2013). In brief, SaOS-2 cells were seed cultured at the density of 3 × 10 3 cells per well in a 96-well culture plate for overnight.…”
Section: Osteosarcomacell Viability Assaymentioning
confidence: 99%
“…Moreover, ROS seem to trigger VEGF expression and the activation of VEGF receptor 2 as well as HIF-1 (hypoxia induced factor-1) induction which consequently stimulates angiogenesis. Hence, by improving antioxidant activity, N. sativa indirectly exerts antiangiogenic effects as well [34]. Endostatin is reportedly responsible, as the major factor, for inhibition of angiogenesis and seems to suppress endothelial cells' proliferation and migration by affecting a variety of genes involved in cell cycle, anti-apoptosis and mitosis.…”
Section: Discussionmentioning
confidence: 99%